2016
DOI: 10.14260/jemds/2016/1138
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Electrocardiography and Treadmill Test in Type 2 Diabetic Patients Without Cardiac Symptoms

Abstract: Coronary artery disease is more common in diabetic population, but can be asymptomatic in many patients and may present with sudden death, myocardial infarction, arrhythmia, silent myocardial ischaemia or heart failure. Early detection of asymptomatic coronary artery disease in Type 2 Diabetes may prevent catastrophic cardiac events. However, periodical thorough clinical examination and resting Electrocardiogram (ECG) may fail to detect coronary artery disease. Noninvasive tests like exercise electrocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The statistical significance of this outcome was established. Both Agarwal et al [12] and Deb et al [16] reported similar findings. Most patients with TMT positivity have been diagnosed with diabetes for more than 10 years, according to the findings of numerous studies conducted by Joshi et al [19] and Swaminathan and Gayathri [20].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The statistical significance of this outcome was established. Both Agarwal et al [12] and Deb et al [16] reported similar findings. Most patients with TMT positivity have been diagnosed with diabetes for more than 10 years, according to the findings of numerous studies conducted by Joshi et al [19] and Swaminathan and Gayathri [20].…”
Section: Discussionsupporting
confidence: 59%
“…According to previous research by Ditchburn et al [18], Deb et al [16], and Joshi et al [19], men made up the majority of study participants.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The demographic characteristics, such as age and gender distribution, in this study, align with findings from prior investigations. In the investigation carried out by Dipankar Deb et al, [7] the predominant demographic consisted of individuals aged 35-44 years. In the study conducted by Amit Daphale et al [8], the average age of the participants was found to be 46.20 years.…”
Section: Resultsmentioning
confidence: 99%